USE OF MEDIA MATERIALS IN THE FOREIGN LANGUAGE CLASSES - Яременко, Ірина (SWorldJournal, 2024)
The paper discusses the use of authentic videofilms in the foreign language classes, their importance for the development of students’ communicative competence, and the problems of their use. Particular attention is paid to film soundtracks, having numero